Oncogenic miR-27a delivered by exosomes binds to SFRP1 and promotes angiogenesis in renal clear cell carcinoma - Yi Hou; Li Fan; Hai Li (Elsevier, 2021)
Exosomes derived from cancer cells have emerged as important mediators of malignant phenotypes of tumors, being involved in the transmission of biological signals between cells. Herein, we intended to clarify the role of exosome-mediated transfer of oncogenic microRNA-27a (miR-27a) in angiogenesis of renal clear cell carcinoma (RCCC). Through bioinformatics analysis, we identified the differentially expressed genes of RCCC and predicted miRNAs targeting SFRP1. We manipulated the expression of miR-27a and/or SFRP1 in RCCC cells to explore their roles in angiogenesis through Cell Counting Kit-8 (CCK-8), Transwell, and Matrigel tubule formation assays. miR-27a loaded in exosomes was overexpressed and downregulated in vitro and in vivo to verify its effect on angiogenesis. SFRP1 was poorly expressed and miR-27a was highly expressed in RCCC tissues, showing a negative correlation. Dual-luciferase assay verified that miR-27a targeted and downregulated SFRP1 expression. Notably, miR-27a enhanced angiogenesis by downregulating SFRP1 expression. miR-27a-loaded exosomes can be delivered from RCCC cells to human umbilical vein endothelial cells (HUVECs). In vitro and in vivo experiments substantiated that miR-27a-loaded exosomes from RCCC cells repressed SFRP1, augmenting the viability, migration, and angiogenesis of RCCC cells. Together, RCCC-derived miR-27a-loaded exosomes inhibit SFRP1 expression and accelerate tumor angiogenesis in RCCC.